Enhancing Halal Procurement Strategies in the Hospitality Industry: Challenges, Solutions, and Future Directions - Rosiana, Eka Nuraisah; Nugraha, Siti Yulia Irani; Wanti, Wanti Arum; Prawira, Mega Fitriani Adiwarna (Integrasi Sains Media, 2025)
The rapid expansion of halal tourism has intensified the need for structured halal procurement in the hospitality industry. However, hotels face significant challenges in maintaining halal compliance due to limited supplier availability, regulatory inconsistencies, financial constraints, and knowledge gaps. This study examines these challenges and proposes strategic solutions for halal procurement efficiency. The findings highlight that hotels in non-Muslim-majority regions struggle with supply chain disruptions caused by a lack of certified halal suppliers and high certification costs. Additionally, inconsistent global halal regulations make standardization difficult for multinational hotel chains, while limited staff training further complicates compliance. This study recommends expanding supplier networks through international partnerships, implementing structured halal training programs, and introducing financial support mechanisms such as tax incentives and certification subsidies to address these barriers. Furthermore, harmonizing global halal certification standards through mutual recognition agreements (MRAs) can enhance regulatory consistency and supply chain transparency. The conceptual framework developed in this study illustrates how halal regulations, consumer preferences, and sustainability considerations drive halal procurement strategies, emphasizing the need for collaborative efforts among hotel operators, policymakers, and certification authorities. Strengthening halal procurement practices will improve consumer trust, operational efficiency, and the competitiveness of halal-certified hotels, positioning the hospitality industry as a key player in the global halal tourism market.